2007
DOI: 10.1007/s12010-007-8018-x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis of Penicillin for 6-APA Production in Three-Liquid-Phase System

Abstract: A dodecane/thermosensitive polymer/water three-liquid-phase system was introduced for enzymatic hydrolysis of penicillin G (Pen G) for 6-aminopenicillanic acid (6-APA). The enzyme was covalently attached to the terminal of PEO-PPO-PEO polymer (L63), which would be transferred into a polymer coacervate phase at high temperature above its "cloud point". 6-APA was primarily resided in the aqueous phase due to its zwitterionic nature. More than 70% phenylacetic acid (PAA) was transferred into the organic phase usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…They are considered as more environmentally-friendly than their volatile, toxic, and organic counterparts. ILs that are regarded as "green" solvents, have received worldwide attention in various elds including catalysis, 16,17 electrochemistry, 18,19 separation, 20,21 chemical synthesis, polymer chemistry and nanotechnology. 22,23 Swatloski et al (2000) reported the use of an ionic liquid (IL) as a solvent for cellulose both for the regeneration of cellulose and for the chemical modication of polysaccharide.…”
Section: Introductionmentioning
confidence: 99%
“…They are considered as more environmentally-friendly than their volatile, toxic, and organic counterparts. ILs that are regarded as "green" solvents, have received worldwide attention in various elds including catalysis, 16,17 electrochemistry, 18,19 separation, 20,21 chemical synthesis, polymer chemistry and nanotechnology. 22,23 Swatloski et al (2000) reported the use of an ionic liquid (IL) as a solvent for cellulose both for the regeneration of cellulose and for the chemical modication of polysaccharide.…”
Section: Introductionmentioning
confidence: 99%